2009
DOI: 10.1016/j.annepidem.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Reasons Why Mothers Do or Do Not Have Their Adolescent Daughters Vaccinated Against Human Papillomavirus

Abstract: PURPOSE The objective of this study was to compare the reasons why mothers do or do not have their adolescent daughters vaccinated against HPV. METHODS Mothers of vaccinated and unvaccinated 11- to 17-year-old girls seen during preventive care visits in outpatient family medicine or pediatric clinics underwent an audiotaped structured telephone interview that used open-ended questions to assess the reasons underlying maternal decisions about HPV vaccination. Qualitative methods categorized maternal responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
174
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 171 publications
(186 citation statements)
references
References 40 publications
9
174
1
2
Order By: Relevance
“…4,19,74,78,79 Indeed, some parents indicated a preference for vaccinating in the preteen years specifically because they viewed adolescents as having little say during this 11 Cross-sectional, online survey rout rout F, M 776 National sample of pediatricians and family physicians Gilkey, 2016 60 Cross-sectional, online survey rout rout F, M 1495 National sample of parents of adolescents (ages 11-17) Gilkey, under review 16 Cross-sectional, online survey rout rout F, M 1484 National sample of parents of adolescents (ages [11][12][13][14][15][16][17] (Continued on next page) time. 18,80 In contrast, other studies found that adolescents did play a role in communication and decision-making in clinical settings, one which increased with age, maturity, and social privilege. 18,27,71,73,76,80 For some parents, the desire to maximize adolescents' role was even a reason for delaying HPV vaccination.…”
Section: Communication Rolesmentioning
confidence: 79%
See 1 more Smart Citation
“…4,19,74,78,79 Indeed, some parents indicated a preference for vaccinating in the preteen years specifically because they viewed adolescents as having little say during this 11 Cross-sectional, online survey rout rout F, M 776 National sample of pediatricians and family physicians Gilkey, 2016 60 Cross-sectional, online survey rout rout F, M 1495 National sample of parents of adolescents (ages 11-17) Gilkey, under review 16 Cross-sectional, online survey rout rout F, M 1484 National sample of parents of adolescents (ages [11][12][13][14][15][16][17] (Continued on next page) time. 18,80 In contrast, other studies found that adolescents did play a role in communication and decision-making in clinical settings, one which increased with age, maturity, and social privilege. 18,27,71,73,76,80 For some parents, the desire to maximize adolescents' role was even a reason for delaying HPV vaccination.…”
Section: Communication Rolesmentioning
confidence: 79%
“…18,80 In contrast, other studies found that adolescents did play a role in communication and decision-making in clinical settings, one which increased with age, maturity, and social privilege. 18,27,71,73,76,80 For some parents, the desire to maximize adolescents' role was even a reason for delaying HPV vaccination. 80 Studies suggested that parent-adolescent decisions were largely concordant and that most dyads ultimately reached agreement about the vaccination decision, but they sometimes looked to providers for guidance in the case of initial disagreement.…”
Section: Communication Rolesmentioning
confidence: 79%
“…Other factors associated with their acceptance were a doctor's recommendation and the fact that they had agreed to previous childhood vaccinations 13. Parents who declined cited reasons such as concerns about side effects13, 20 and long‐term safety 19, 21. They also believed that their daughters were too young13, 21 or they did not perceive that there was a risk of HPV infection 21.…”
mentioning
confidence: 99%
“…Parents who declined cited reasons such as concerns about side effects13, 20 and long‐term safety 19, 21. They also believed that their daughters were too young13, 21 or they did not perceive that there was a risk of HPV infection 21. Another common barrier to accepting the vaccination was insufficient knowledge or information about the virus and the vaccine 13, 19.…”
mentioning
confidence: 99%
“…Studies show that the influence of accurate information about vaccines is maximized when conveyed from physician to parent or patient [75]. In prioritizing this approach over general health advertisement campaigns, physicians retain their position as patient advocates rather than agents of the government who must enforce policy.…”
Section: Inflammatory False Claimsmentioning
confidence: 99%